The Effectiveness of the Role of the Radiology Department in Conducting and Interpreting Medical Diagnostic Tests - Abdalmawla Atwan Jarallah Almalawi, Naif Ahmed H Alqouzi, Fayad Awad Alsharari, Mansour Falah Mohammed, Madallah Musaad Alsharari; Majed Mufleh Mashi Al Shararai, Tawfeeg Abdu Mousa Ageely, Waleed Salih Al.Zahrani, Ali Abdullah Aseeri, Othman Najm Alothman (Journal of International Crisis and Risk Communication Research, 2024)